URGENSI KONSEP A PRIORI CONSTITUTIONAL DALAM PEMBENTUKAN UNDANG - UNDANG DI INDONESIA (PERBANDINGAN NEGARA PERANCIS DAN CHILI): 1. Pengertian Konsep a Priori Constitutional Review - Vijae Yehezkiel Simanjuntak (CV Rewang Rencang, 2024)
The laws that are formed and enforced must be in accordance with the mandate of the Constitution in order to guarantee the citizens. In practice, in 2023 alone, the Constitutional Court has granted 18 requests for judicial review of the Law. This indicates the poor quality of the legislature in Indonesia. The method used in this study is normative research or doctrinal legal research. The approaches used include the Legislative Approach, the Conceptual Approach and the Comparative Approach of Chile, Hungary and Austria. The data collection technique uses literature studies. The results of the study indicate the urgency of implementing a Priori Constitutional Review based on the principle of judicial restraint in the process of forming laws in Indonesia as a preventive effort against legal products that conflict with the Constitution.